Cleaner production of mulberry spun silk yarns via a shortened and gassing-free production route. (1st January 2021) - Yin, R.; Xiang, Y.F.; Zhang, Z.H.; Tao, X.M.; Gluck, J.M.; Chiu, K.; Lam, W.
Abstract: The green production of textiles via an eco-friendly approach has recently gained considerable interest. As a derivative industry of silk manufacturing, spun silk utilizes waste materials generated in different processes of silk production, which is considered as the re-use of silk waste. The spun silk industry is facing several problems now, including environmental pollution, low production efficiency, increased labor intensity, significant material waste, and excessive energy consumption. This study presents an environment-friendly production route to produce mulberry spun silk yarns, by eliminating the gassing process that burns away surface hairs and neps. The gassing process not only generates odors, dust, and gas discharges but also results in significant material wastage and high production cost. The key is a modified ring spinning technology to achieve low yarn hairiness and neps; thus the yarn produced no longer requires gassing. The number of processing steps is also reduced to nine from twelve compared to the traditional silk spinning system. The modified 60 Nm mulberry spun silk yarns show a comparable tenacity of 26.33 cN/tex, evenness of 9.96%, neps (+200%) of 18 per 1 km, and a slightly worse hairiness S3 value of 74 per 100 m, compared with the conventional gassed ones. The plain knitted fabrics made by the modified yarns also reveal a 1.5 grade higher pilling resistance, similar mechanical and thermal properties, and a slightly hairier surface appearance than the conventional ones. The new processing route greatly reduces carbon footprint and achieves significant savings in materials, manpower, and energy, which may shed new light on the industrial manufacturing of mulberry spun silk yarns. Graphical abstract: Image 1 Highlights: An eco-friendly production process to manufacture mulberry spun silk yarns. Excellent properties of yarns and fabrics comparable with conventional ones. Elimination of greenhouse gas emission, odor, and dust pollution due to gassing. Significant savings achieved in materials, manpower, and energy.